Morphological, Ethno biological and Phytopharmacological Attributes of Tridax procumbensLinn. (Asteraceae): A Review - Ghosh, P.; Biswas, S.; Biswas, M.; Dutta, A.; Sil, S.; Chatterjee, S. (International Journal of Scientific Research in Biological Sciences, 2019)
Tridax procumbens Linn. is an widespread herbaceous weed distributed throughout India. It is commonly known as coat buttons, is also dispensed as Bhringraj, and used as Ayurvedic medicine for liver disorders and hair growth. The plant is an annual or perennial herbaceous weed, found mainly in the croplands, disturbed areas, lawn, and roadsides. Literature survey suggested that the various parts of the plant were reported to possess phytochemical compounds like alkaloids, carotenoids, flavonoids, saponins, fumaric acid, β-sitosterol, and tannins. It was richly endowed with oleanolic acid, and high content of sodium and potassium are also present. Bioactive components like luteolin, glucoluteolin, quercetin, and isoquercetin also have been reported from its flowers. Primary plant pigments such as chlorophyll and carotenoids also analyzed from leaves. So, it is well known for several potential pharmacological activities like anti-microbial, anti-oxidant, wound healing, insecticidal, hepato-protective, anti-diabetic, immune modulating, anti-cancer, anti-dysentery, anti-inflammatory, and anti-hair fall. The present review study deals with natural habitat, taxonomical, phytochemical, pharmacological and toxicological activities of Tridax procumbens. This study may be helpful for identification and preparation of a clear profile of the plant which may open new avenues in the medical field in the treatment of various diseases.